2008
DOI: 10.1007/s10765-008-0512-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PTFE Using Advanced Thermal Analysis Techniques

Abstract: Polytetrafluoroethylene (PTFE) is a synthetic fluoropolymer used in numerous industrial applications. It is often referred to by its trademark name, Teflon. Thermal characterization of a PTFE material was carried out using various thermal analysis and thermophysical properties test techniques. The transformation energetics and specific heat were measured employing differential scanning calorimetry. The thermal expansion and the density changes were determined employing pushrod dilatometry. The viscoelastic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(72 citation statements)
references
References 5 publications
9
63
0
Order By: Relevance
“…(The interface thermal resistance typically increases by ~ 50% between room temperature at T = 130 K. either saturated or decreasing with decreasing temperature and v c is expected to be only weakly temperature dependent, Eqtn. (6) implies that  also increases with decreasing temperature, as would be expected for phonon-phonon scattering. This is again consistent with being larger than the interlayer spacing.…”
Section: Rubrene Results and Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…(The interface thermal resistance typically increases by ~ 50% between room temperature at T = 130 K. either saturated or decreasing with decreasing temperature and v c is expected to be only weakly temperature dependent, Eqtn. (6) implies that  also increases with decreasing temperature, as would be expected for phonon-phonon scattering. This is again consistent with being larger than the interlayer spacing.…”
Section: Rubrene Results and Discussionmentioning
confidence: 64%
“…6,7 While such low values of κ may limit the use of these organic semiconductors in microelectronics, they are favorable for possible thermoelectric applications. 7 Because rubrene has a layered structure, it is also important to know its interplane thermal conductivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It does not adhere to other materials and has the lowest coefficient of friction of all solids. However, clinical studies involving PTFE acetabular cups in the total hip replacement prostheses showed unacceptably high wear and distortion [37]. The wear debris resulted in extensive tissue reaction and even formation of granuloma.…”
Section: Polymers Compositesmentioning
confidence: 99%
“…Diffusion of CO 2 was most significant in the DOC cooling coil, a 1.5-m long portion of tubing positioned right after the combustion column, probably because this tube carries hot carrier gas and water vapor that increases PTFE diffusivity (Blumm et al 2010). Other non-PTFE components were tested for microleaks or CO 2 diffusion but were not found to be significant contributors.…”
Section: Sample Oxidationmentioning
confidence: 99%